PDB file parser and structure class implemented in Python - Hamelryck, Thomas; Manderick, Bernard (Bioinformatics, 2003)
The biopython project provides a set of bioinformatics tools implemented in Python. Recently, biopython was extended with a set of modules that deal with macromolecular structure. Biopython now contains a parser for PDB files that makes the atomic information available in an easy-to-use but powerful data structure. The parser and data structure deal with features that are often left out or handled inadequately by other packages, e.g. atom and residue disorder (if point mutants are present in the crystal), anisotropic B factors, multiple models and insertion codes. In addition, the parser performs some sanity checking to detect obvious errors. Availability: The Biopython distribution (including source code and documentation) is freely available (under the Biopython license) from http://www.biopython.org